Quasi-static and dynamic characterization of ultrafine-grained 2017A-T4 aluminium alloy processed by accumulative roll bonding - Halimi, A.; Boudiaf, A.; Hemmouche, L.; Medjahed, A.; Tria, D.E.; Henniche, A.; Djeghlal, M.E.A.; Baudin, T. (Archives of Mechanics, 2021)
In this study, novel composite strips based on 2017A-T4 aluminium alloy (Al-Cu-Mg) produced by accumulative roll bonding (ARB) were developed. The microstructure and mechanical properties of the ultrafine-grained sheets under quasistatic and dynamic loadings were investigated. The initial microstructure characterization with an Optical Microscope and a Scanning Electron Microscope indicated that the ARBed sheets formed a compact material with the homogeneous and identical thickness for the individual bonded layers. Besides, the presence of precipitates was identified in all the processed strips with diverse sizes, quantities and distribution. Moreover, from Electron Back Scatter Diffraction, the microstructure was noticeably refined with increasing theARBcycles to reach 1.7 µm the grain size at the fifth cycle. The microhardness measurement and the tensile test were carried out for both natural ageing and ARBed specimens. Accordingly, the tensile stress acts on the individual layers rather than the entire sample that conduct to a reduction in the overall properties for the ARBed strips. Furthermore, a stabilization in the mechanical properties for the three first ARB cycles was noted, whereas, the domination of the dynamic recrystallization was responsible for a significant drop after the fourth cycle which is considered as the transition state. The characteristics of the compression deformation were examined under dynamic and quasi-static loadings conditions by using the Split–Hopkinson Pressure Bar system and the universal testing machine, respectively. The strain hardening behaviour was investigated using the Hollomon analysis. It was found that the thermal softening played a crucial role when compared to the strain hardening for all the studied strips. Moreover, the strain rate under the dynamic loading has a minor effect on the stress flow of the ARBed sheets compared to the as-received material.